ANALISIS BREAK EVEN POINT USAHA PETERNAKAN AYAM PEDAGING DI DESA UJUNG BARU KECAMATAN BATI-BATI KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Hastirullah Fitrah (Universitas Lambung Mangkurat, 2013)
This study aims to determine the cost, revenue, profit and break even point broiler livestock in the ujung baru village of Bati Bati during 1 periods maintenance. The method used was a survey method with observation techniques, while the sampling method using purposive random sampling technique; wherein the desired criteria is based on a certain subject characteristic or trait previously known population; namely in this study is the independent. Number of samples that meet the above criteria as much as 6 breeder. Total cost of broiler farm of Rp 568,518,665.00 with an average of Rp 94,753,110.83 / year / breeder. Value of the Acceptance of Rp 751.935.500/tahun and an average of Rp 125,322,583.33 / breeder. Gains derived by Rp 183,416,835.00 / year with an average of Rp 30,569,472.50 / breeder. Break Even Point or breakeven point broiler farm in the village of New Edge in quantities occurs at the level of production of 4836.21 kg / rancher with a sales volume of USD 36,621,987.38 / breeder.